2002
DOI: 10.1051/0004-6361:20011613
|View full text |Cite
|
Sign up to set email alerts
|

Far-infrared emission from intracluster dust in Abell clusters

Abstract: Abstract. The ISOPHOT instrument aboard ISO has been used to observe extended FIR emission of six Abell clusters. Strip scanning measurements with crossing position angles centered on the clusters were carried out at 120 µm and 180 µm. The raw profiles of the I120 µm/I180 µm surface brightness ratio including zodiacal light show a bump towards Abell 1656 (Coma), dips towards Abell 262 and Abell 2670, and are without clear structure towards Abell 400, Abell 496, and Abell 4038. After subtraction of the zodiacal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 96 publications
5
50
0
Order By: Relevance
“…Stickel et al 2002). It is expected that, due to sputtering by energetic photons, such dust would have a very short lifetime in the ICM environment (Draine & Salpeter 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Stickel et al 2002). It is expected that, due to sputtering by energetic photons, such dust would have a very short lifetime in the ICM environment (Draine & Salpeter 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, nowadays the only claimed (and still controversial) detection of this IR emission comes from the studies on the Coma cluster of Stickel et al (1998Stickel et al ( , 2002, who measured a diffuse dust mass of M dust ≈ 10 7 M , while other attempts resulted in non detections (see, e.g., Bai et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Quillen et al (1999) suggested integrated emission from the cluster galaxies as the most likely source for the detected signal at the centre of Coma. Stickel et al (2002) replied that if this was indeed the case, the same signal should have been detected in all clusters observed. The absence of any signature for intra-cluster dust in five clusters and the rather low inferred dust mass in Abell 1656 indicates that intra-cluster dust is probably not responsible for the excess X-ray absorption reported in cooling flow clusters (White et al 1991).…”
Section: A Diffuse Intra-cluster Dust Component ?mentioning
confidence: 91%
“…But only upper-limits or occasionally, and with marginal significance, global or average cluster FIR emission, could constrain scenarios for the role of dust in the physics of the clusters as a whole. Stickel et al (1998Stickel et al ( , 2002) used ISOPHOT to observe extended FIR emission of six Abell clusters. Strip scanning measurements were performed at 120 µm and 180 µm.…”
Section: A Diffuse Intra-cluster Dust Component ?mentioning
confidence: 99%